Learners’ opportunities to learn algebra content in grade 9 - Mtshali, Hloniphile T. P.; Ogbonnaya, Ugorji I.; Sekao, David (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
The aim of this research was to examine the extent to which algebra content was taught to Grade 9 mathematics learners in four schools within a specific education district in Gauteng province, South Africa. This qualitative case study was conducted within the framework of interpretive qualitative research. Document analysis was employed as the method of data collection. The findings of the study indicate that the coverage of algebra content in the participating schools did not align with the prescribed curriculum. Consequently, it can be inferred that the learners did not have adequate opportunities to learn the algebra content. It is recommended that teachers adhere to the curriculum guidelines when delivering instruction.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (2) (2023)
Keywords: Algebra; Algebraic; Expressions; Algebraic language; Content coverage; Factorisation; Opportunity to learn; Algebra -- Study and teaching; Mathematics -- Study and teaching (Secondary) -- South Africa -- Gauteng